Photo-Excited Metasurface for Tunable Terahertz Reflective Circular Polarization Conversion and Anomalous Beam Deflection at Two Frequencies Independently - Zhixiang Xu; Cheng Ni; Yongzhi Cheng; Linhui Dong; Ling Wu (Nanomaterials, 2023)
In this paper, a photo-excited metasurface (MS) based on hybrid patterned photoconductive silicon (Si) structures was proposed in the terahertz (THz) region, which can realize the tunable reflective circular polarization (CP) conversion and beam deflection effect at two frequencies independently. The unit cell of the proposed MS consists of a metal circular-ring (CR), Si ellipse-shaped-patch (ESP) and circular-double-split-ring (CDSR) structure, a middle dielectric substrate, and a bottom metal ground plane. By altering the external infrared-beam pumping power, it is possible to modify the electric conductivity of both the Si ESP and CDSR components. By varying the conductivity of the Si array in this manner, the proposed MS can achieve a reflective CP conversion efficiency that ranges from 0% to 96.6% at a lower frequency of 0.65 THz, and from 0% to 89.3% at a higher frequency of 1.37 THz. Furthermore, the corresponding modulation depth of this MS is as high as 96.6% and 89.3% at two distinct and independent frequencies, respectively. Moreover, at the lower and higher frequencies, the 2π phase shift can also be achieved by respectively rotating the oriented angle (αi) of the Si ESP and CDSR structures. Finally, an MS supercell is constructed for the reflective CP beam deflection, and the efficiency is dynamically tuned from 0% to 99% at the two independent frequencies. Due to its excellent photo-excited response, the proposed MS may find potential applications in active functional THz wavefront devices, such as modulators, switches, and deflectors.